Effect of sowing dates and genotypes on the yield of coriander (Coriandrum sativum L.) - Moniruzzaman, M; Rahman, MM; Hossain, MM; Karim, AJM Sirajul; Khaliq, QA (Bangladesh Journal of Agricultural Research, 2015)
A field experiment on coriander (Coriandrum sativum L.) taking five sowing dates viz. November 01, November 16, December 01, December 16 and December 31 and four selected genotypes viz. CS001, CS007, CS008 and CS011 was conducted during the Winter season of 2009-10 at Bangabandhu Sheikh Mujibur Rahman Agricultural University to study heat efficiency for the crop. The crop sown on November 16 and the genotype CS011 showed the highest heat use efficiency for dry matter, seed and stover yield. Heat use efficiency for dry matter as well as seed yield increased from November 01 to November 16 and then decreased with delayed sowing. November 16 sowing coupled with CS011 gave the maximum heat use efficiency for seed yield. Growing Degree Days (GDD) showed a positive linear response with dry matter accumulation and coefficient of regression was high in November 16 sowing as well as in CS011. Heat use efficiency showed a negative linear response with maximum (y = 2.058 0.054, R2 = 0.682*), minimum (y = 2.123 0.070x, R2 = 0.687*) and mean (y = 2.13 o.063x, R2 =0.709*) temperature but positive linear response with relative humidity (y = 0.074x 5.593, R2 = 0.702*). Bangladesh J. Agril. Res. 40(1): 109-119, March 2015